The Effect of Processing Temperature of Simple Steam Jacket on The Quality of White Spotted Whipray Rays Liver Oil - Wahyu Nur Widiyanto; Ratna Ibrahim; Apri Dwi Anggo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
The application of high temperature steam jacket system in the industrial fish liver processing makes the product is of poor quality. The quality data of Rays liver oil processed by simple jacket steam with temperature above 80°C are currently not available. This research aimed to determine temperature of simple steam jacket processing method to the quality of White Spotted Whipray Rays liver oil. The differences of processing temperatures affected significantly the value of free fatty acid, peroxide, and yield; but did not affected significantly on the water content and the organoleptic value specification products except on turbidity. The most optimum processing temperature of Rays liver oil was at 60 °C for 20 minutes with the content of free fatty acids 0.68%, the peroxide 0,57 meq/kg, and the moisture of the oil 0%. The product had yield 37.88%, the sensory value 7.97 ≤ μ ≤ 8.35 and omega-3: 23.44%, as well as omega-6: 10.19%. Keywords: Fish liver oil, simple steam jacket, temperature